Analisis Laporan Keuangan Dalam Menilai Kinerja Keuangan Pada PT. Artha Lestari Engineering - Nindy Pertiwi; Johanis Johanis; Meldianus N J Lenas (Jurnal Riset dan Inovasi Manajemen, 2024)
Nindy Pertiwi, 2024. "Analysis of Financial Statements as a Basis for Evaluating Financial Performance: A Case Study of PT. Artha Lestari Engineering." Supervised by Johanis dan Meldilians NJ Lenas. This study aims to analyze financial statements to assess the financial performance of PT. Artha Lestari Engineering. Data were collected from PT. Artha Lestari Engineering's financial statements for the period 2019-2023 using a financial ratio analysis approach. The results of the ratio analysis reveal that the liquidity ratio initially experienced a significant decline but improved in the final year. Although the liquidity ratio remains high, the initial decline indicates challenges in liquidity management. The solvency ratios remain low, indicating a reliance on equity rather than debt, with fluctuations in these ratios reflecting the stability of this reliance. Activity ratios show stability with slight decreases, while Inventory Turnover and Receivable Turnover experienced fluctuations and declines, respectively. Profitability performance increased significantly, reflecting improvements in operational efficiency and profitability during the study period.